Gentle strength training in rehabilitation of breast cancer patients compared to conventional therapy - Schmidt, Thorsten; Weisser, Burkhard; Jonat, Walter; Baumann, Freerk Theeagnus; Mundhenke, Christoph (Anticancer Research, 2012)
Movement therapy during the rehabilitation of breast cancer has become more important over the last years. Patients and Methods: In a randomized controlled study the feasibility of gentle strenght training was compared to conventional gymnastic exercises during rehabilitation of breast cancer patients. The aim oft this study was to identify alternative sports intervention in the treatment of breast cancer patients. The intervention group (IG) was lifting standardized weights weekly (50% of h1RM), while the control group (CG) received conventional gymnastic exercises. A bicycle ergometry adjusted to the WHO system was performed with all participants at study entry (T0), after three (T1) and six months (T2). The quality of life was measured by standardized report forms (EORTC QLQ C30 Version 3 and BR23). Results: Both methods showed a slight improvement in submaximal endurance performance, a significant improvement in the subjective feeling of effort (IG: 75 W: <0.01, CG: 75 W <0.01), in psychosocial and psychological parameters like quality of life (IG: <0.01, CG <0.01) and in fatigue (IG: <0,01, CG: <0.01). Conclusion: This study shows positive effects for gentle strength lifting in the rehabilitation of breast cancer patients and turned out to be a probate alternative to gymnastic exercises.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Breast cancer; Gentle strength training; Physical activity; Quality of life; Rehabilitation